Exploring Loan Sharks in Online Peer-to-Peer Lending Applications: A Case Study of Vietnam - Nguyen, Oanh Van; Lai, Cong Van; Luong, Hai Thanh; Le, Toan Quang (International Journal of Criminology and Sociology, 2021)
Online peer-to-peer lending applications have emerged in some recent years in Vietnam, where the consumer lending market is potential for financial companies. This country faces challenges to control the online lending business. As a result, criminals find loopholes in the legal system on this business to commit loan sharks. This article targets to explore the nature of the connection between a loan shark and online peer-to-peer lending applications through interviewing with police officials in their specific operation investigated. The findings highlight a close structure of criminal groups related to loan sharks via this lending platform and a comprehensive profile of borrowers. These findings suggest some recommendations for fighting against this crime effectively in the coming time.